Role of the Peroxisome Proliferator Activated Receptors in Hypertension. Issue 7 (2nd April 2021) - Fang, Shi; Livergood, M. Christine; Nakagawa, Pablo; Wu, Jing; Sigmund, Curt D.
Abstract : Nuclear receptors represent a large family of ligand-activated transcription factors which sense the physiological environment and make long-term adaptations by mediating changes in gene expression. In this review, we will first discuss the fundamental mechanisms by which nuclear receptors mediate their transcriptional responses. We will focus on the PPAR (peroxisome proliferator-activated receptor) family of adopted orphan receptors paying special attention to PPARγ, the isoform with the most compelling evidence as an important regulator of arterial blood pressure. We will review genetic data showing that rare mutations in PPARγ cause severe hypertension and clinical trial data which show that PPARγ activators have beneficial effects on blood pressure. We will detail the tissue- and cell-specific molecular mechanisms by which PPARs in the brain, kidney, vasculature, and immune system modulate blood pressure and related phenotypes, such as endothelial function. Finally, we will discuss the role of placental PPARs in preeclampsia, a life threatening form of hypertension during pregnancy. We will close with a viewpoint on future research directions and implications for developing novel therapies.